Development of Grousers with a Tactile Sensor for Wheels of Lunar Exploration Rovers to Measure Sinkage. (26th March 2014) - Iizuka, Kojiro; Sasaki, Tatsuya; Yamano, Mitsuhiro; Kubota, Takashi
This paper presents a grouser developed for the wheels of lunar exploration rovers to measure sinkage. The wheels, which are intended to traverse loose soil such as lunar regolith, contain grousers that transfer thrust to the wheels and thus to the body of the rover. The interaction between the wheel (with grousers) and the loose soil can be described using a kinematic model. When traversing loose soil, the wheel sinks into the soil, which necessitates knowledge of the entrance angle needed in order to avoid this problem. If the entrance angle is known, the sinkage can be measured in real time before adverse conditions occur. Because of the importance and usefulness of detecting the entrance angle of the wheel, we herein propose a grouser with an embedded tactile sensor. A strain gauge on the surface of the grousers serves as the tactile sensor. In order to confirm the precision of the proposed grouser, we have performed tests on a rigid surface and loose soil surfaces.